Potentially traumatic experiences pre-migration and adverse pregnancy and childbirth outcomes among women of Somali- and Kurdish-origin in Finland - Satu Majlander; Tarja I. Kinnunen; Eero Lilja; Mika Gissler; Anu E Castaneda; Lara Lehtoranta; Päivikki Koponen (BMC, 2023)
Abstract Background Women in precarious conditions in their countries of origin, especially those who have left the country as refugees, may have been victims of serious mental and physical violence. These potentially traumatic experiences may threaten women's reproductive health. This study examines the prevalence of potentially traumatic experiences pre-migration and female genital mutilation/cutting (FGM/C) and their associations with adverse reproductive outcomes among migrant women of Somali- and Kurdish-origin who have been pregnant in Finland. Methods Survey and register data of the participants of the Finnish Migrant Health and Wellbeing Study (Maamu), conducted in 2010-2012, were used. Women of 18 to 64 years of age, 185 Somali- and 230 Kurdish-origin, who had at least one pregnancy or birth in Finland were included in the analysis. The survey data were linked to the Finnish Medical Birth Register, the Register of Induced Abortions, and the Care Register for Health Care until 2018. For each outcome, logistic regression was used and adjusted for age, body mass index, time lived in Finland, and the number of births. Results A total of 67% of Somali-origin and 71% of Kurdish-origin women had experienced potentially traumatic experiences pre-migration and 64% of Somali- and 32% of Kurdish-origin women had also undergone FGM/C. In Kurdish-origin women, complications during pregnancy (e.g. bleeding in the first trimester, known or suspected fetal abnormality, signs of fetal hypoxia, death of the fetus and other problems) were significantly more common among women without potentially traumatic experiences (70%) than among women with potentially traumatic experiences (48%) (p-value 0.005). No associations between potentially traumatic experiences or FGM/C and other adverse reproductive outcomes were observed among Somali- or Kurdish-origin women. Conclusion Past trauma is common among Somali- and Kurdish-origin women and this needs to be evaluated in maternity care. However, we found no association between potentially traumatic experiences pre-migration and adverse reproductive outcomes.